2012
DOI: 10.1007/s11999-011-2011-y
|View full text |Cite
|
Sign up to set email alerts
|

The Otto Aufranc Award: Demineralized Bone Matrix Around Porous Implants Promotes Rapid Gap Healing and Bone Ingrowth

Abstract: Background Noncemented revision arthroplasty is often complicated by the presence of bone implant gaps that reduce initial stability and biologic fixation. Demineralized bone matrix has osteoinductive properties and therefore the potential to enhance gap healing and porous implant fixation. Questions/purposes We determined at what times and to what extent demineralized bone matrix promotes gap healing and bone ingrowth around a porous implant. Methods We inserted porous titanium implants into the proximal meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Histologic evidence of osteoblasts penetrating the surface of the DBM granules denoted the material’s ability to support osteoblastic cell adhesion ( 21 ). Results showed that the density of the newly formed bone inside surgically created gaps filled with DBM reached 93% of native bone density after 12 weeks ( 22 ). Moreover radiographic evidence of new bone formation after using injectable DBM during sinus elevation surgery was seen following a 6 months healing period ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Histologic evidence of osteoblasts penetrating the surface of the DBM granules denoted the material’s ability to support osteoblastic cell adhesion ( 21 ). Results showed that the density of the newly formed bone inside surgically created gaps filled with DBM reached 93% of native bone density after 12 weeks ( 22 ). Moreover radiographic evidence of new bone formation after using injectable DBM during sinus elevation surgery was seen following a 6 months healing period ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…With the material’s ability to induce differentiation of mesenchymal cells to form bone as well as serve as a scaffold for osteoprogenitor cells attachment ( 22 , 24 , 25 ), the combined effect of adding both DBM and β-TCP to augment the deficient horizontal alveolar ridge was evaluated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The third requirement is the open-type porosity structure suitable for vascularization and cell immobilization during the tissuesubstitution process. 18 For proof of concept, we developed material providing for the quick release of wound-healing accelerators-insulin and the relatively slow release of collagen-as the model of morphogenesis proteins. Whereas insulin, which is responsible for wound healing, must be released rapidly in rst several days, the rate of release for collagen, which is responsible for tissue substitution, must be rather slow.…”
Section: Introductionmentioning
confidence: 99%